Politik Hukum Penanggulangan Bencana - Zuzi Kurnia Ramadhani; Rangga Prayitno; Radiyan Rahim; Yumai Wendra (Ekasakti Jurnal Penelitian dan Pengabdian, 2024)
Indonesia is identified as a country with very high potential of natural disaster. Such disaster can give impact to national economy,welfare, and state politics, so that people urge the government to pay better attention to disaster management by providing adeqquate legal instruments.This situation has furtherled to the making of LawNo.24/2007 on Disaster Management. Never theless, there several problems remain regarding basic legal politics of the Law No. 24/2007 and substance of the legal politics in disaster management. Both kinds of the problems should be, according the writer, properly addressed by using legal approaches. This essay arguesthat legal politic sofnatural disaster handlingis the construction law and the legal establish menton disaster management. in substance, this legal politics provide a paradigm shift in disaster management. There are also problems regarding contra dictionamong related existing laws, authority, and institutions in disaster management. Therefore, it is necessary to review the legal policy of disaster management and revisionof the Law No. 24/2007.